Adapting to Local Context and Managing Relationships: A Case Study of a Multinational SDP Partnership in Bahrain. Issue 2 (18th May 2022) - AlKhalifa, Hussa K.; Collison, Holly
Abstract: This paper considers the managerial process of a sport-for-development event in a geographic area that has rarely been investigated from a Sport for Development and Peace (SDP) academic perspective. Specifically, an examination of the relationships between multinational SDP organizations and a local SDP entity in managing and implementing an event in Bahrain is explored. Reflecting on the broader contextual aspects of the case, participant observation over 4 days and interviews with those involved from all organizations are used to reflect upon and build an understanding of how SDP management and relationships are localized in this regional setting. Initial findings indicate potential for further cooperation and expertise sharing between international organizations, with a particular need for understanding roles and partnership structures as well as being cognizant of local contexts and needs. Significantly, donor-recipient tensions are identified, and the positive impact of partnership-strengthening workshops are considered.